Lectotypification and epitypification of Morella cerifera (L.) Small (Myricaceae) - Parra Osorio Carlos Alberto (Caldasia)
Se establece la tipificación formal de Morella cerifera (L.) Small (Myrica cerifera L.). Se escoge un lectótipo y un epitipo luego del estudio de los elementos del protólogo. The formal typification of Morella cerifera (L.) Small (Myrica cerifera L.) was established. A lectotype and an epitype werw selected after the study ofprotologue's elemens.